Neonatal appendicitis: A rare presentation of necrotising enterocolitis in a term infant - Rao, Subhash; Saxena, Nandita; Salvii, Kumar; Chavan, Vishwas (Indian Journal of Child Health, 2022)
Appendicitis is one of the rare causes of acute abdomen in the neonatal age group. We describe one such case in a term baby and discuss its pathogenesis as one of the presentations of Necrotising Enterocolitis.